Pendekatan Psikologi Sastra dalam Mengkaji Naskah Drama Satu Babak Berjudul “Bentrokan dalam Asrama Karya Achdiat Karta Mihardja” - Aulia, Nabila Rahma; Novitasari, Fitra; Saharani, Elsa; Hasanah, Della Al; Rosialasa, Nabila Ajeng Fransisca; Rahmi, Iklima Hilda; Putra, Adita Widara (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
This article examines a one-act play entitled “Bentrok dalam Asrama” by Achdiat Karta Mihardja with a literary psychology approach, specifically Sigmund Freud's psychoanalysis theory. This research aims to reveal the personality dynamics of the characters through the interaction of id, ego, and superego, as well as to understand the internal and external conflicts experienced by each character. The method used is descriptive qualitative with analysis techniques in the form of literature study of dialog, monologue, and conflicts that arise in the drama. The results of the analysis show that Hasan and Hadi dominate the id aspect through impulsive and manipulative actions, while Anas reflects a strong superego through his patient and empathetic attitude. Hadi's character experiences significant ego development as the story progresses. The play not only depicts conflicts between characters, but also represents complex inner conflicts as a reflection of human psychological dynamics. This research enriches the understanding of the play by emphasizing the importance of the literary psychology approach in analyzing the personality and conflict of characters in literary works.